Generating universal anti-CD19 CAR T cells with a defined memory phenotype by CRISPR/Cas9 editing and safety evaluation of the transcriptome - Pavlovic, Kristina; Carmona-Luque, MDolores; Corsi, Giulia I.; Maldonado-Pérez, Noelia; Molina-Estevez, Francisco J.; Peralbo-Santaella, Esther; Cortijo-Gutiérrez, Marina; Justicia-Lirio, Pedro; Tristán-Manzano, María; Ronco-Díaz, Víctor; Ballesteros-Ribelles, Antonio; Millán-López, Alejandro; et al. (Frontiers in Immunology, 2024)
Chimeric antigen receptor-expressing T cells (CAR T cells) have transformed cancer treatment, especially in B cell malignancies. However, the reliance on autologous T cells for CAR T therapy brings limitations, including increased costs and, in some cases, reduced efficacy, with associated adverse effects tied to cell phenotype. To address these challenges, we developed a strategy for generating universal and safe anti-CD19 CAR T cells with a defined memory phenotype. Our approach employs CRISPR/Cas9 for targeted elimination of the B2M and TRAC genes, reducing graft-versus-host and host-versus-graft, combined with selection of less differentiated T cells to enhance the stability and persistence of universal CAR T cells. A safety evaluation conducted through our CRISPRroots transcriptome analysis pipeline provides robust evidence of successful gene knockout and the absence of unintended off-target effects impacting gene expression or transcriptome sequence. This underpins the relevance of CRISPRroots as a pioneering tool for on/off-target and transcriptome analysis of RNA-seq data for genome editing experiments. In vitro experiments confirmed the successful generation of functional universal CAR T cells that combine potent lytic capacity against tumor cells with a less pronounced cytokine secretion profile.In conclusion, we established a potent pipeline for the manufacturing of safe universal CAR T cells with an advantageous memory phenotype.